2019
DOI: 10.5812/jhealthscope.88589
|View full text |Cite
|
Sign up to set email alerts
|

Health Care Utilization Inequality in a Mixed Public-Private Health Care System: An Insight from the National Survey in Iran

Abstract: Background: Equitable health care utilization is a pillar of the Universal Health Coverage (UHC) and is also a concern to policymakers. Measuring and quantifying the inequalities are essential in assessing the progress toward achieving the UHC goals. Several studies have focused on overall measures of unfair inequality in health care utilization. The overall approaches to outpatient and inpatient services are not representative of the differences in health care usage in public and private sectors in a mixed he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 36 publications
(50 reference statements)
2
1
0
Order By: Relevance
“…However, no significant differences in the inequality of OHSU were found in households with a university-graduated head. These findings are consistent with Hassanzadeh et al, 59 and Zakeri et al 75 which showed that less educated individuals had more OHSU compared to highly educated ones. Unlike our findings, Homaie Rad et al 76 and Rezaei et al 24 showed that when the education level of individuals or heads of households increased, the dental health service utilization increased as well, with this inequality being to the detriment of the less privileged classes in terms of their socioeconomic status.…”
Section: Discussionsupporting
confidence: 92%
“…However, no significant differences in the inequality of OHSU were found in households with a university-graduated head. These findings are consistent with Hassanzadeh et al, 59 and Zakeri et al 75 which showed that less educated individuals had more OHSU compared to highly educated ones. Unlike our findings, Homaie Rad et al 76 and Rezaei et al 24 showed that when the education level of individuals or heads of households increased, the dental health service utilization increased as well, with this inequality being to the detriment of the less privileged classes in terms of their socioeconomic status.…”
Section: Discussionsupporting
confidence: 92%
“…Interestingly, a third of participants had low-income (< 3000 riyals), reflecting the fact that the university hospital is a general hospital. This is in line with a previous report that found socioeconomic status to be a major factor affecting health care utilization in Iran (21). Treatment and consultation are free of charge in general hospitals; accordingly, the majority of Saudis prefer to visit general hospitals, especially for chronic diseases, where consecutive visits are required (22).…”
Section: Discussionsupporting
confidence: 90%
“…In comparison with regional and global patterns, our study ndings are aligned with ndings from the global literature on private sector health service use in mixed health systems. For example, a study assessing health care utilisation in the mixed health system of Iran showed pro-rich patterns for the private sector and pro-poor patterns in the public sector (29). Similar patterns were found in different African contexts and other LMICs, as well as across European countries (30)(31)(32)(33).…”
Section: Limitationsmentioning
confidence: 73%